'Modern' Madrasa: Deoband and Colonial Secularity - Ingram, Brannon D. (Historical social research, 2019)
This article situates the emergence of the Deoband movement, an Islamic revivalist movement based at India’s Dar al-‘Ulum Deoband madrasa (seminary), within concepts of colonial secularity in British India. It shows how the decline of first Mughal and then British patronage for Islamic learning, as well as the post-1857 British policy of non-interference in ‘religious’ matters, opened up a space for Deobandi scholars to re-conceive the madrasa as a ‘religious’ institution rather than one engaged in the production of civil servants, to reimagine the ‘ulama’ as stewards of public morality rather than professionals in the service of the state, and to reframe the knowledge they purveyed as ‘religious’ knowledge distinct from the ‘useful’ secular knowledge promoted by the British. The article treats this production of ‘religious’ knowledge and space as discourse of distinction similar to those explored elsewhere in this HSR Special Issue.